Edukasi Dampak Penggunaan Gadget pada Generasi Alpha di Sekolah Dasar - Nuril Wildah; Bisma Ardika; Naysilla Meirani; Jasmine Suci Maharani; Zahra Deby Anatasya; Mochammad Raffi Krisna Putra; Setyono Setyono; Oria Alit Farisi; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The use of gadgets among elementary school-aged children has been increasing and has the potential to affect students' learning concentration, particularly during classroom learning activities. Uncontrolled gadget use can lead to various problems in the teaching and learning process. This study aims to describe both the positive and negative impacts of gadget use on elementary school children, especially sixth-grade students, in relation to their learning concentration. This study employs a qualitative approach, in which data were collected through observation, interviews, and documentation. The research subjects were sixth-grade students at SDN Trebungan, Bondowoso Regency. The results indicate that gadget use can have positive impacts, such as facilitating access to learning information; however, it can also cause negative impacts, including decreased learning focus, dependency on gadgets, and reduced effective study time. Based on these findings, it can be concluded that gadget use among elementary school students requires adequate supervision from parents and teachers to maintain students' learning concentration and minimize negative effects.